Does home-based pulmonary rehabilitation improve functional capacity, peripheral muscle strength and quality of life in patients with bronchiectasis compared to standard care? - José, Anderson (Braz J Phys Ther, 2017)
BACKGROUND: Home-based pulmonary rehabilitation is a promising intervention that may help patients to overcome the barriers to undergoing pulmonary rehabilitation. However, home-based pulmonary rehabilitation has not yet been investigated in patients with bronchiectasis. OBJECTIVES: To investigate the effects of home-based pulmonary rehabilitation in patients with bronchiectasis. METHODS: An open-label, randomized controlled trial with 48 adult patients with bronchiectasis will be conducted. Interventions: The program will consist of three sessions weekly over a period of 8 weeks. Aerobic exercise will consist of stepping on a platform for 20 min (intensity: 60–80% of the maximum stepping rate in incremental step test). Resistance training will be carried out using an elastic band for the following muscles: quadriceps, hamstrings, deltoids, and biceps brachii (load: 70% of maximum voluntary isometric contraction). Control: The patients will receive an educational manual and a recommendation to walk three times a week for 30 min. All patients will receive a weekly phone call to answer questions and to guide the practice of physical activity. The home-based pulmonary rehabilitation group also will receive a home visit every 15 days. Main outcome measures: incremental shuttle walk test, quality of life, peripheral muscle strength, endurance shuttle walk test, incremental step test, dyspnea, and physical activity in daily life. The assessments will be undertaken at baseline, after the intervention, and 8 months after randomization. DISCUSSION: The findings of this study will determine the clinical benefits of home-based pulmonary rehabilitation and will contribute to future guidelines for patients with bronchiectasis. Trial registration:www.ClinicalTrials.gov (NCT02731482). https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S00060X6&selectaction=Edit&uid=U00028HR&ts=2&cx=1jbszg